Bundled-optode method for detection of brain activity in functional near-infrared spectroscopy - Hoang-Dung Nguyen; Keum-Shik Hong (2016 16th International Conference on Control, Automation and Systems (ICCAS), 2016)
This paper presents a multiple optodes arrangement method in functional near-infrared spectroscopy (fNIRS) for measuring the absolute concentrations of oxy-hemoglobin and deoxy-hemoglobin. To remove physiological noises, short/long-separation detectors are used in the spatially resolved spectroscopy approach. The proposed method is applied to measure the brain activity of five healthy male subjects in mental arithmetic tasks targeting the prefrontal cortex. The obtained results reveal that the proposed method can be used as an alternative approach to the conventional modified Beer-Lambert law. Most of all, the proposed method can remove physiological noises better than the conventional method. Finally, the present work can be extended to a 3D imaging of brain if the entire brain can be covered by neighboring optodes massively and multiple data processing units for real-time computation providing much improved spatial resolution.